Utilization of Rainwater into Fresh Water through Electrolysis Method for Communities Affected by Tidal Flooding - Qudus, Nur; Harianingsih, Harianingsih; Sugiyarto, Bambang; Kristianto, Virgiawan Adi; Siswoyo, Mohammad Pujo; Pangestu, Indra Sakti; Erliana, Savira Rinda; Ubay, Isnina Noor (Journal of Community Empowerment, 2024)
Water is an essential resource, crucial for human survival and well-being. In coastal areas like Sayung District, Demak Regency, Central Java, accessing clean drinking water is a significant challenge. This problem is made worse by environmental issues such as tidal flooding, known locally as "rob," which causes the groundwater to become salty and undrinkable. To address this urgent issue, the UNNES (Universitas Negeri Semarang) community service team has launched a project aimed at using rainwater as a source of safe drinking water. The project follows several key steps: first, assessing the current situation to understand the needs and resources of the community; second, training local residents on how to use electrolysis to convert rainwater into potable water; and third, evaluating the effectiveness of the training and the results achieved. The outcomes of this project have been highly positive. The community has gained valuable knowledge about rainwater treatment technologies, developed skills in building electrolysis equipment, and successfully produced fresh water from rainwater. This initiative not only helps to meet the immediate water needs of the community but also provides them with a sustainable solution for their future water needs.